2020
DOI: 10.3390/diagnostics11010007
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gut, Vaginal, and Urinary Microbiome in Urinary Tract Infections: From Bench to Bedside

Abstract: The current paradigm of urinary tract infection (UTI) pathogenesis takes into account the contamination of the periurethral space by specific uropathogens residing in the gut, which is followed by urethral colonization and pathogen ascension to the urinary bladder. Consequently, studying the relationship between gut microbiota and the subsequent development of bacteriuria and UTI represents an important field of research. However, the well-established diagnostic and therapeutic paradigm for urinary tract infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 95 publications
1
71
0
5
Order By: Relevance
“…Firstly, the composition of microorganisms is often disturbed by influencing factors such as host age, BMI, and endocrine status. Meštrović T. et al (2020) have observed that vaginal flora is affected by intestinal flora. Furthermore, the sample size was insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the composition of microorganisms is often disturbed by influencing factors such as host age, BMI, and endocrine status. Meštrović T. et al (2020) have observed that vaginal flora is affected by intestinal flora. Furthermore, the sample size was insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies are done from UTI patients and obtain similar organisms from gut, vaginal, or urethral flora. This occurs as the gut flora colonizes the urethra and then the organism ascends in a retrograde manner from the urethra, thereby causing UTI [ 26 ]. In this study, we found similar Enterococcus species of organism from the vaginal discharge and urine isolate in three patients.…”
Section: Discussionmentioning
confidence: 99%
“…Auch spielt das vaginale Milieu eine zentrale Rolle und bildet mit dem Darm als Ursprung auch fakultativ pathogener Erreger eine entscheidende Achse in der Pathogenese weiblicher HWI [ 2 ]. Ein bidirektionaler Austausch von Darm und urogenitalem Mikrobiom ist somit entscheidend zum Verständnis und der Prävention rHWI [ 30 ].…”
Section: Diskussionunclassified